2015
DOI: 10.1126/sciadv.1500055
|View full text |Cite
|
Sign up to set email alerts
|

Wear biomechanics in the slicing dentition of the giant horned dinosaur Triceratops

Abstract: Triceratops developed complex dental morphology, allowing it to become a dominant herbivore in the late Mesozoic era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 37 publications
2
60
0
Order By: Relevance
“…As peritubular dentine is harder than intertubular dentine [38], an increase in dentine tubules would increase the hardness of the dentine directly below the DEJ. This agrees with reports of elevated hardness in mantle dentine in hadrosaurs [2] and ceratopsians [3], even though mantle dentine is typically softer than primary dentine [39]. Therefore, the derived condition of hard dentine at the DEJ in ornithischians is a combination of the lack of globular mantle dentine and the increased density of narrow dentine tubules.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As peritubular dentine is harder than intertubular dentine [38], an increase in dentine tubules would increase the hardness of the dentine directly below the DEJ. This agrees with reports of elevated hardness in mantle dentine in hadrosaurs [2] and ceratopsians [3], even though mantle dentine is typically softer than primary dentine [39]. Therefore, the derived condition of hard dentine at the DEJ in ornithischians is a combination of the lack of globular mantle dentine and the increased density of narrow dentine tubules.…”
Section: Discussionsupporting
confidence: 90%
“…The hardness and elasticity of dentine can change depending on the angle of the dentine tubules within the dentinal matrix [30]. Considering the unique wear patterns formed in ornithischian tooth batteries and the increased hardness of dentine at the DEJ, ornithischian teeth were well adapted for grinding plant material [2,3,11]. The elastic properties of mantle dentine [39], absent in ornithischians but present in saurischians, probably protected the teeth of carnivorous theropods from fracture during feeding on prey items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Varriale () and Mallon and Anderson (), as in the current study, noted slight differences within ceratopsids as well, such as between centrosaurines and chasmosaurines. Erickson et al () also showed that the complex microscopic tissues in ceratopsian dentitions possessed novel recessed central regions along the slicing surface, which would have helped reduce friction during occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in dental microscopic wear of basal ceratopsians shows considerable variability in wear orientation (e.g., “clinolineal” in psittacosaurids [Sereno et al, ]; palinal in Archaeoceratops and other basal ceratopsians [Varriale, ]); however, this has been suggested to show a plausible trend toward the more complex orthopalinal feeding seen in ceratopsids (Varriale, ). The tooth battery in ceratopsids has a complex internal structure (Erickson et al, ) and is secondarily mesiodistally straighter (although not perfectly), oriented parallel to its counterpart. The tooth rows in ceratopsids (convergent in hadrosaurids) extend farther distally, medial to the coronoid process, which both elongates the tooth row and provides greater mechanical advantage in occlusion (Ostrom, ; Tanoue et al, ; Mallon and Anderson, ; Nabavizadeh, ).…”
Section: Marginocephaliamentioning
confidence: 99%